Switching the uniaxial magnetic anisotropy by ion irradiation induced compensation - Yuan, Ye; Amarouche, Teyri; Xu, Chi; Rushforth, Andrew; Böttger, Roman; Edmonds, Kevin; Campion, Richard; Gallagher, Bryan; Helm, Manfred; von Bardeleben, Hans Jürgen; Zhou, Shengqiang (IOP Publishing, 2018)
In the present work, the uniaxial magnetic anisotropy of GaMnAsP is modified by helium ion irradiation. According to the micro-magnetic parameters, e.g. resonance fields and anisotropy constants deduced from ferromagnetic resonance measurements, a rotation of the magnetic easy axis from out-of-plane [001] to in-plane [100] direction is achieved. From the application point of view, our work presents a novel avenue in modifying the uniaxial magnetic anisotropy in GaMnAsP with the possibility of lateral patterning by using lithography or focused ion beam.